Characterization of antioxidant,antimicrobial, anticancer property and chemical composition of phyllanthus urinaria linn. leaf extract. - Lee Seong Wei; Wendy Wee; Julius Young Fu Siong; Desy Fitrya Syamsumir (2012 • vol.2 • 36 - 40, 2012)
This study was carried out to characterize antimicrobial, antioxidant and anticancer activities of Phyllanthus urinaria leaf extract as well as its chemical composition. The main objective of the present study is to reveal the medicinal values of P. urinaria leaf. Antimicrobial property of P. urinaria leaf extract was revealed by using two fold microdilution method whereas antioxidant activity of the extract was determined with α, α- diphenyl-β-picrylhydrazyl (DPPH) radical scavenging method. The anticancer property of the plant extract was revealed through Colorimetric MTT (tetrazolium) assay against human breast adenocarcinoma (MCF-7). Chemical compounds of the plant extract were screening and identiﬁed by using gas chromatography-mass spectrometry (GC-MS). The result of the present study showed that the MIC values of the present study ranged from 31.25 to 125 mg/l in which the plant extract was found able to inhibit the growth of all the tested bacterial isolates namely A. hydrophila, E. tarda, E. coli, Flavobacterium sp., Klebsiella sp., P. aeruginosa, Salmonella sp., V. alginolyticus, V. cholerae and V. parahaemolyticus. The value of IC50 of the plant extract against DPPH was 0.282 ± 0.23 ppt and no anticancer activity was observed in the present study. A total of 9 chemical compounds was successfully identiﬁed with Phenol 46.05 % and 2-pentanone, 4-hydroxy-4-methyl- 14.69 % were the major compounds. The ﬁndings of the present study showed that the antimicrobial and antioxidant properties of the plant extract are promising.